2021
DOI: 10.1021/acs.macromol.1c01879
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Synthesis and Degradation of Functionalized Poly(4-allyloxymethyl-β-propiolactone)s

Abstract: The chemical synthesis of degradable poly(β-hydroxyalkanoate) (PHA) produced by microorganisms allows the control of the solubility, crystallinity, hydrophobicity, degradability, thermal, and mechanical properties by introducing functionality on the side chain. Herein, we synthesized a PHA derivative containing a pendant allyl group via the anionic ring-opening polymerization of a 4-allyloxymethyl-β-propiolactone (AMPL) monomer, which was prepared via the carbonylation of allyl glycidyl ether. The AMPL monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…PHAs can also be produced via chemical synthesis from lactones through ring-opening polymerization (ROP) in which better control of properties of resultant polymers is achievable. This approach utilizes initiators, monomers such as β-lactones and cyclic esters, and metal catalysts for polymerization to occur . Diverse homopolymers and copolymers may be produced using a clever combination of monomers and catalysts. , A recent study reported the possibility of using nonmetallic catalysts in ring-opening polymerization of β-butyrolactone (BBL).…”
Section: Poly(hydroxyalkanoates (Pha) Origin Types Properties and Bio...mentioning
confidence: 99%
See 1 more Smart Citation
“…PHAs can also be produced via chemical synthesis from lactones through ring-opening polymerization (ROP) in which better control of properties of resultant polymers is achievable. This approach utilizes initiators, monomers such as β-lactones and cyclic esters, and metal catalysts for polymerization to occur . Diverse homopolymers and copolymers may be produced using a clever combination of monomers and catalysts. , A recent study reported the possibility of using nonmetallic catalysts in ring-opening polymerization of β-butyrolactone (BBL).…”
Section: Poly(hydroxyalkanoates (Pha) Origin Types Properties and Bio...mentioning
confidence: 99%
“…In another study, Yu et al recently reported PHA polymerized from 4-allyloxymethyl-β-propiolactone monomer (AMPL) through anionic-ROP using organocatalysts. The resultant poly­(AMPL) was modified through photoactivation and achieved excellent degradation profiles in soil and seawater mediums . Makaguchi and colleagues used diphenyl phosphate (DPP) as a catalyst and 3-phenyl-1-propanol as an initiator in toluene to perform ROP of δ-valerolactone (δ-VL) and ε-caprolactone (ε-CL) at room temperature.…”
Section: Poly(hydroxyalkanoates (Pha) Origin Types Properties and Bio...mentioning
confidence: 99%
“…26 Yu and co-workers investigated the post-polymerisation modification of both allylic side chains and crotonic end groups of poly(4-allyloxymethyl-β-propiolactone). 27…”
Section: Introductionmentioning
confidence: 99%
“…26 Yu and co-workers investigated the post-polymerisation modification of both allylic side chains and crotonic end groups of poly(4-allyloxymethyl-β-propiolactone). 27 Further, phosphines can be regarded as potentially interesting reaction partners for crotonates as they participate in Michael-addition reactions and are commonly used as catalysts. 28,29 Galkin and co-workers reported on the functionalisation of unsaturated carboxylic acids using phosphines.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, various macromolecular designs using organic catalysts have enabled researchers to synthesize many kinds of vinyl polymers. Anionic polymerizations, conventional alkyllithiums, and Grignard reagents , are well-known as the most accessible candidates for this purpose, and many controlled polymerizations of vinyl monomers have already been reported. Moreover, along with the recent progress in advanced radical and cationic polymerizations, anionic polymerizations have also advanced. These progressions would not have been possible without Lewis pair polymerization (LPP) .…”
Section: Introductionmentioning
confidence: 99%